2012
DOI: 10.1111/j.1755-3768.2012.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond (FS) laser vision correction procedure for moderate to high myopia: a prospective study of ReLEx® flex and comparison with a retrospective study of FS‐laser in situ keratomileusis

Abstract: ABSTRACT.Purpose: To present our initial clinical experience with ReLEx Ò flex (ReLEx) for moderate to high myopia. We compare efficacy, safety and corneal higher-order aberrations after ReLEx with femtosecond laser in situ keratomileusis (FS-LASIK). Methods: Prospective study of ReLEx compared with a retrospective study of FS-LASIK. ReLEx is a new keratorefractive procedure, where a stromal lenticule is cut by a femtosecond laser and manually extracted. Forty patients were treated with ReLEx on both eyes. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 20 publications
5
101
0
2
Order By: Relevance
“…9 In a comparative study between SMILE and FS-LASIK, Vestergaard et al found that CDVA was better than 20/20 in 85% of eyes in the SMILE group and in 83% of eyes in the LASIK group postoperatively. 10 However, in a comparative study between SMILE and FS-LASIK, Lin et al found no significant difference between eyes attaining a UCVA of 20/20 in the two groups. 11 Hu et al found 48 eyes in the SMILE group and 37 eyes in the LASIK group showing a gain of one line.…”
Section: Discussionmentioning
confidence: 99%
“…9 In a comparative study between SMILE and FS-LASIK, Vestergaard et al found that CDVA was better than 20/20 in 85% of eyes in the SMILE group and in 83% of eyes in the LASIK group postoperatively. 10 However, in a comparative study between SMILE and FS-LASIK, Lin et al found no significant difference between eyes attaining a UCVA of 20/20 in the two groups. 11 Hu et al found 48 eyes in the SMILE group and 37 eyes in the LASIK group showing a gain of one line.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study on 54 eyes found no regression during the first 6 months after surgery. 8 Similarly, no regression has been found during the first 3-6 months after 500 kHz FLEx 10,11,13,14 or for 1 year after 200 kHz FLEx. 15,16 A prospective, randomised, paired-eye study comparing SMILE and FLEx documented no significant regression between 1 week and 6 months.…”
Section: Refractive Outcomementioning
confidence: 99%
“…ingrowth and monocular ghost images. 10,11,19 Recently, we found irregular postoperative topography in 18 of 1,574 eyes, giving rise to ghost images in six cases. 23 Topography-guided PRK was performed in four of these eyes, ameliorating the symptoms in three cases.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to: (i) suboptimal laser photo-disruption of the stromal fibers that subsequently causes interface scattering due to traumatic dissection [9] -this can be rectified by optimization of the laser settings, (ii) micro-distortions in Bowman's layer following lenticule removal [10], and (iii) transient increased stromal keratocyte activity at the interface resulting from the stromal pocket irrigation [11]. Hence, smooth, atraumatic dissection, of the stromal lenticule and sweeping of the anterior cap both to disperse the microdistortions to the periphery, and also to aid in drainage of the pocket fluid, can enhance the postoperative visual recovery.…”
mentioning
confidence: 99%